Australian guidelines for the prevention and treatment of posttraumatic stress disorder: Updates in the third edition. (March 2022) - Phelps, Andrea J; Lethbridge, Ros; Brennan, Sue; Bryant, Richard A; Burns, Penelope; Cooper, John A; Forbes, David; Gardiner, Joanne; Gee, Graham; Jones, Kim; Kenardy, Justin; Kulkarni, Jayashri; et al.
Objective: This paper describes the development of the third edition of the National Health and Medical Research Australian Guidelines for the Prevention and Treatment of Acute Stress Disorder, posttraumatic stress disorder and Complex posttraumatic stress disorder, highlighting key changes in scope, methodology, format and treatment recommendations from the previous 2013 edition of the Guidelines. Method: Systematic review of the international research was undertaken, with GRADE methodology used to assess the certainty of the evidence, and evidence to decision frameworks used to generate recommendations. The Guidelines are presented in an online format using MAGICApp. Results: Key changes since the publication of the 2013 Guidelines include a new conditional recommendation for Child and Family Traumatic Stress Intervention for children and adolescents with symptoms within the first 3 months of trauma, and a strong recommendation for trauma-focused cognitive behaviour therapy for the child alone or with a caregiver, for those with diagnosed posttraumatic stress disorder. For adults with posttraumatic stress disorder, strong recommendations are made for specific types of trauma-focused cognitive behaviour therapy and conditional recommendations are made for five additional psychological interventions. Where medication is indicated for adults with posttraumatic stress disorder, venlafaxine is now conditionally recommended alongside sertraline, paroxetine or fluoxetine. Conclusion: These Guidelines, based on systematic review of the international literature, are intended to guide decision making for practitioners, service planners, funders and those seeking treatment for trauma related mental health concerns. For an Australian Guideline, a critical limitation is the absence of research on the treatment of Australian Aboriginal and Torres Strait Islander peoples. The new online format of the Australian posttraumatic stress disorder Guidelines means that they can be updated as sufficient new evidence becomes available.